'Phoney Beatlemania has bitten the dust': The punk generation's love–hate relationship with the Fab Four. (24th August 2012) - Ogg, Alex
This article explores the manner in which the punk generation qualified and then recalibrated its initial vilification of the Beatles, the supreme canonical figures in British pop history. It uses primary and secondary interview sources to contextualize the dialogue, both explicit and implied, between the two camps. In so doing, it attempts to situate the Beatles on the punk landscape and assess their function as totemic anti-heroes within the subculture. The article then examines the underlying influence Lennon-McCartney may have wielded on punk-era songwriting and looks at all four individual Beatles' responses to punk, attempting to reconcile the mutual negotiation that took place.